Experiências de Ensino e Aprendizagem : estratégia para a formação online de professores iniciantes no Programa de Mentoria da UFSCar - Pieri, Glaciele dos Santos de (2010)
This research investigated three teachers learning in their beginning of career at the first years of elementary school and an expert teacher the mastermind who have taken part of the Mastermind Program (MP) at UFSCar Teacher´s website. The initial focus were the Experiences of Teaching and Learning towards the literacy process, formative and investigative activity which has required the planning, implementation and evaluation of educative proposals to be made in common sense between a beginner and the mastermind from the specific difficulties indicated by the learner. The research was established through a study of case and it was based on a qualitative approach. The data sources were MP initial and final questionnaires, the productions developed by the beginners about literacy process along the MP, the interactions between the mastermind and the learner (considered online narratives) and the messages attachments. It was also established an actual interview with the mastermind and an online interview procedures sent to the beginner teachers. The theoretical references had as basis the teachers´ learning and their professional development, the knowledge basis for teaching, the online formation and the characteristics of the educators´ career phase. The conclusions of this research indicate the importance of the Teaching and Learning Experiences for the learning process of the beginners and also the urgency to promote the following of newcomers having as a start point the dilemmas and the difficulties found by them in this moment of their careers.